ALTERNATIVE RELIGION IN PRETORIA: NEW FORMS OF CHRISTIANITY PART I - Clasquin, M. (Scriptura, 1999)
This article is part of a larger research project on patterns of religious pluralism in the city of Pretoria, and is based on field research conducted in in the period 1993-1995 by the author, Prof JS Kruger and Mr MS (Victor) Molobi. Material extraneous to the main thrust of the project is being published in a series of articles. This article describes the rise of alternative religious forces in Pretoria during the late nineteenth and early twentieth centuries and how these faiths have accommodated to the religious environment of the city. Part I deals with those groups that, while perhaps unorthodox, still base themselves on the Christian tradition and ethos, these being the New Apostolic Church, Latter-Day Saints (Mormons), Adventists and Jehovah's Witnesses. Part II will take a look at a different and new influence, namely those traditions new to the city that base themselves on Eastern thinking.